Correction: robust Bayesian fluorescence lifetime estimation, decay model selection and instrument response determination for low-intensity FLIM imaging - Rowley, M; Coolen, A; Vojnovic, B; Barber, P (Public Library of Science, 2016)
The images for Figs 5 and 6 are incorrectly switched. The image that appears as Fig 5 should be Fig 6, and the image that appears for Fig 6 should be Fig 5. The figure captions appear in the correct order.